Pearls of experience for safe and efficient hospital practices in otorhinolaryngology—head and neck surgery in Hong Kong during the 2019 novel coronavirus disease (COVID-19) pandemic - Ryan H. W. Cho; Zenon W. C. Yeung; Osan Y. M. Ho; Jacky F. W. Lo; Alice K. Y. Siu; Wendy M. Y. Kwan; Zion W. H. To; Anthony W. H. Chan; Becky Y. T. Chan; Kitty S. C. Fung; Victor Abdullah; Michael C. F. Tong; et al. (Journal of Otolaryngology - Head and Neck Surgery)
Abstract The 2019 novel coronavirus disease (COVID-19) epidemic originated in Wuhan, China and spread rapidly worldwide, leading the World Health Organization to declare an official global COVID-19 pandemic in March 2020. In Hong Kong, clinicians and other healthcare personnel collaborated closely to combat the outbreak of COVID-19 and minimize the cross-transmission of disease among hospital staff members. In the field of otorhinolaryngology—head and neck surgery (OHNS) and its various subspecialties, contingency plans were required for patient bookings in outpatient clinics, surgeries in operating rooms, protocols in wards and other services. Infected patients may shed severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) particles into their environments via body secretions. Therefore, otolaryngologists and other healthcare personnel in this specialty face a high risk of contracting COVID-19 and must remain vigilant when performing examinations and procedures involving the nose and throat. In this article, we share our experiences of the planning and logistics undertaken to provide safe and efficient OHNS practices over the last 2 months, during the COVID-19 pandemic. We hope that our experiences will serve as pearls for otolaryngologists and other healthcare personnel working in institutes that serve large numbers of patients every day, particularly with regard to the sharing of clinical and administrative tasks during the COVID-19 pandemic.